I’DÂD KITÂB AL-NAHW AL-TA’LÎMÎ ‘ALÂ DHAU’I TAJDÎD AL-NAHW ‘INDA SYAUQI DHAYF LI THALABAH JÂMI’AH PALOPO AL-ISLÂMIYYAH AL-HUKÛMIYYAH BI SULAWESI AL-JANÛBIYYAH - Wahyuddin Wahyuddin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
This research was aimed to: Produce nahwu teaching book based on Syauqi Dhayf’ theory. Measure the eligibility of the book. Measure the affectivity of the book.This research was  research and development model as laid out by Borg and Gall was modified. The analyses qualitative databy using Miles and Huberman’s theory, and  analyses quantitative data by using T-Test. the result of this research is: Among the characteristics of teaching materials developed are by utilizing inductive approach. Such approach uses materials which are based on reformation theory by Syauqi Dhayf who neglects i’râb taqdiry and mahally, removes ‘âmil in i’râb, and redefines nahwu topic. The developed teaching book is eligible to be used in teaching nahwu based on validation by experts nahwu, arabic, and teaching design. which achieved  very good score. The developed teaching book is effective in improving the grades of students based on T-Test that counted: 20,014 bigger than T table: 2,101 and its significant grade: 0,000 smaller than alpha: 0,050. It means there is a great difference of exam’s results between before and after implementation.